Lee Kuan Yew : the man and his dream - Liow, Joseph Chinyong (2015)
Lee Kuan Yew’s indomitable spirit and pragmatism in ensuring Singapore’s survival was driven equally by an idealism and vision of an independent island that would be an oasis in an arid Southeast Asia.